Pengaruh Servicescape Terhadap Kepuasan Konsumen Uda Fes Kuliner’s Cabang Juanda di Kota Padang - Toberi Vonika; Rose Rahmidani (Universitas Negeri Padang, 2020)
This study aims to know and prove how much influence theservicescape to consumer satisfactions cafe uda fes kuliner’s branch Juanda in Padang City.This type of research is causal assosiative. The population in this study consumer uda fes kuliner’s branch Juanda in Padang City with the sampling technique used perposive sampling. The samples were taken using Cochran formula with 100 respondents. This sampling technique is based on nonprobability sampling method. The type of data used in this study is primary data. Data analysis technique used multiple regression analysis technique using SPSS version 21.00. The results of this study indicate that: 1) Ambient conditions has a significant effect on consumer satisfaction (0,035<0,05), 2) Spatial Layout and Functionshas a positive significant effect on consumer satisfaction(0,008>0,05), 3) Signs, Symbols, and Artifact has a positive significant effect on consumer satisfaction (0,018<0,05). Keywords: ambient conditions, spatial layout and functions, signs symbols and artifact, consumer satisfaction